The Feasibility and Practicality of a Digital Enrichment Book for News Text Listening Comprehension Oriented toward The Pancasila Student Profile Supported by an AI-Powered Help Page - Desyfa Cahya Aina; Subyantoro (International Journal of Science and Society, 2026)
Teaching news text listening comprehension in junior high school requires supplementary teaching materials that provide targeted practice, adequate listening materials, and analytical activities that support the strengthening of students’ character. This study aims to describe the feasibility and practicality of a digital enrichment book for news text listening comprehension oriented toward the Pancasila Student Profile, supported by an AI-powered help page. This study employs the Research and Development (R&D) method based on Sugiyono’s model up to the seventh stage, namely product revision following a limited pilot test. Data were collected through media expert validation, content expert validation, student response questionnaires, and product usage observations. Data were analyzed using qualitative and quantitative descriptive methods with percentage calculations. The results indicate that the product achieved a feasibility percentage of 97% from media experts and 97.5% from content experts, placing it in the “highly feasible” category. The practicality results showed a percentage of 90% based on student responses and 89.71% based on product usage observations, placing it in the “highly practical” category. Revisions to the product were made regarding the user guide, internet connection instructions, notes for teachers, content reinforcement, and clarification on the use of the AI-powered Help Page. Thus, the product is suitable and practical for use as supplementary teaching material for learning to listen to news texts and supports the dimensions of critical thinking, independence, and creativity.